Drought effects on cotton (Gossypium hirsutum L.) fibre quality and fibre sucrose metabolism during the flowering and boll‐formation period. (16th January 2020) - Gao, Min; Snider, John L.; Bai, Hua; Hu, Wei; Wang, Rui; Meng, Yali; Wang, Youhua; Chen, Binglin; Zhou, Zhiguo
Abstract: The cotton ( Gossypium hirsutum L.) crop is an indeterminate species that is most sensitive to drought stress during the flowering and boll‐formation stage of development. To evaluate the effect of water deficit on fibre quality and carbon metabolism at different fruiting branches (FB), multiple controlled experiments were conducted. The cotton cultivar Siza 3 was used under three soil relative water content (SRWC): control (CK, SRWC (75 ± 5) %), moderate drought stress (MDS, SRWC (60 ± 5) %) and severe drought stress (SDS, SRWC (45 ± 5) %) treatment, imposed at the beginning of the flowering of FB6–7 . Fibre quality was significantly affected by drought level and fruiting branch location on the plant. Compared to the CK, under MDS and SDS, sucrose content and sucrose synthase (SuSy) activity decreased prior to 24 days post‐anthesis (DPA; the fibre elongation phase), which caused low fibre turgor pressure. This decreased the rate of fibre elongation and final fibre length. Moreover, from 24 to 38 DPA (during fibre thickening), low fibre sucrose content led to insufficient UDP‐glucose (UDPG; uridine diphosphate glucose) for cellulose synthesis. Furthermore, more of the existing UDPG was allocated to the synthesis of callose instead of cellulose, which resulted in lower cellulose accumulation and decreased fibre strength. The magnitude of the drought stress effect on fibre qualities, as well as the formation process, was strongly influenced by fruiting branch position, where differences were most pronounced for fruiting branches further away from the base of the plant.